USE OF E-COMMERCE IN MICRO-ENTERPRISES (MIE) OF CLOTHING AND ACCESSORIES TRADE IN CIUDAD DEL ESTE - Andrés Arévalos Barreto, Arnaldo; Fabiola Cabrera Estigarribia, Liz; Felisa Garcete Caballero, Perla (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this study is to analyze the efficiency of E-commerce in the organization of the operational work of micro-companies of clothing and accessories trade located in Ciudad del Este. Likewise, the research has a mixed approach, being the level of the descriptive study. Likewise, as a data collection instrument, a structured survey with closed and open alternatives applied to six clothing and accessories stores located in the Carolina neighborhood of km 7 of Ciudad del Este was used. At the same time, an interview is conducted with one of the Owner Manager, taking into account the valuable information obtained from the experience of implementing e-commerce in the organization of operational work in a microenterprise. The work exposes the types of e-commerce currently used, the advantages and disadvantages that electronic commerce offers to micro-enterprises and the websites or social networks used for product marketing activity. The results of the field work made it possible to demonstrate the efficiency of e-commerce in the organization of the operational work of the clothing and accessories trade micro-enterprises located in Ciudad del Este.